2006
DOI: 10.1002/humu.20349
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for 3-methylcrotonyl-CoA carboxylase deficiency: population heterogeneity ofMCCA andMCCB mutations and impact on risk assessment

Abstract: New technology enables expansion of newborn screening (NBS) of inborn errors aimed to prevent adverse outcome. In conditions with a large share of asymptomatic phenotypes, the potential harm created by NBS must carefully be weighed against benefit. Policies vary throughout the United States, Australia, and Europe due to limited data on outcome and treatability of candidate screening conditions. We elaborated the rationale for decision making in 3-methylcrotonyl-coenzyme A (CoA) carboxylase deficiency (MCCD), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 48 publications
6
48
0
2
Order By: Relevance
“…Stadler et al recently reported that there was no correlation between phenotypes and genotypes in MCC deficiency (Stadler et al 2006). From these findings and our results, we conjecture that factors other than the genotype at the MCC loci, such as modifying genes and environmental factors, may have a major influence on the MCC deficiency phenotype.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Stadler et al recently reported that there was no correlation between phenotypes and genotypes in MCC deficiency (Stadler et al 2006). From these findings and our results, we conjecture that factors other than the genotype at the MCC loci, such as modifying genes and environmental factors, may have a major influence on the MCC deficiency phenotype.…”
Section: Discussionsupporting
confidence: 70%
“…Enzyme deficiency can result from mutations in either the MCCA or MCCB gene (MIM 210200 and MIM 210210, respectively). Investigators have so far reported 28 MCCA and 41 MCCB mutation alleles, including missense, nonsense, frameshift, and splice site mutations (Stadler et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…diastolic, BP blood pressure, ECG electrocardiogram, TTE transthoracic echocardiography, LVMI left ventricle mass index (normal value ¼ <115 for males and <95 for females), LVEF left ventricular ejection fraction (normal value¼ > 55), Symp. symptoms, PE pulmonary embolism (Stadler et al 2006). The listed prevalences and incidences are conservative estimates, because we only report on carnitinedeficient 3-MCCd cases and not everyone in the Faroe Islands participated in the voluntary screening programme.…”
Section: Discussionmentioning
confidence: 99%
“…Increased renal excretion of 3-hydroxyisovalerylcarnitine is a natural way of excreting toxic intermediary metabolites that interfere with normal metabolism at the cost of low plasma carnitine levels (Roschinger et al 1995). Among organic acidurias, 3-MCCd is the most frequently diagnosed disorder at neonatal tandem mass spectrometry (MS/MS) screening (Koeberl et al 2003;Schulze et al 2003;Wilcken et al 2003;Stadler et al 2006;Lam et al 2013). The 3-MCC enzyme consists of two subunits, a and b, encoded by the MCCC1 and MCCC2 genes, located at 3q25-q27 and 5q12-q13, respectively (Baumgartner et al 2001;Gallardo et al 2001;Holzinger et al 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation